The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/resp.13704
|View full text |Cite
|
Sign up to set email alerts
|

Obesity hypoventilation syndrome treated with non‐invasive ventilation: Is a switch to CPAP therapy feasible?

Abstract: Background and objective Obesity hypoventilation syndrome (OHS) can be treated with either continuous positive airway pressure (CPAP) or non‐invasive ventilation (NIV) therapy; the device choice has important economic and operational implications. Methods This multicentre interventional trial investigated the safety and short‐term efficacy of switching stable OHS patients who were on successful NIV therapy for ≥3 months to CPAP therapy. Patients underwent an autotitrating CPAP night under polysomnography (PSG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 35 publications
0
15
0
3
Order By: Relevance
“…This increased cost was mainly driven by inpatient costs required for NIV titration. However, CPAP can fail as a first‐line treatment or as a second‐line treatment in patients with OHS . In our study, despite a mild baseline hypercapnia and despite a significant improvement of the AHI, mean time spent with an oxygen saturation <90% was high at 2 months (31% and 33% in the AVAPS‐AE and ST groups, respectively).…”
Section: Discussionmentioning
confidence: 57%
“…This increased cost was mainly driven by inpatient costs required for NIV titration. However, CPAP can fail as a first‐line treatment or as a second‐line treatment in patients with OHS . In our study, despite a mild baseline hypercapnia and despite a significant improvement of the AHI, mean time spent with an oxygen saturation <90% was high at 2 months (31% and 33% in the AVAPS‐AE and ST groups, respectively).…”
Section: Discussionmentioning
confidence: 57%
“…However, the present network meta‐analysis found no significant inter‐PAP difference in the reduction of hospital or ED admissions. Given that CPAP has been shown to be more cost‐effective than other forms of NIV (Masa et al., 2019), and that at least one study (Arellano‐Maric et al., 2019) has shown that it is feasible to switch most stable patients with OHS from NIV to CPAP therapy, CPAP definitely has the potential to significantly reduce healthcare costs at the population level. However, in reality in the clinical setting, faced with the pressing issue of the degree of hypercapnia, patient preference, multiple PAP options and the ease of getting a PAP device covered by insurance, clinicians are likely to take a more personalised approach.…”
Section: Discussionmentioning
confidence: 99%
“…Arellano-Maric et al report that patients with obesity hypoventilation syndrome (OHS) treated with noninvasive ventilation (NIV) can be safely switched to continuous positive airway pressure (CPAP) in a recent publication in Respirology. 1 The results of their study suggest that CPAP is preferred over NIV in a majority of patients. However, a sizeable minority of patients (12; 29%) included in their observational trial failed to step-down from NIV to CPAP.…”
mentioning
confidence: 97%